Physical and Mechanical Properties of Self-Compacting Concrete (SCC) with Pineapple Leaf Fibre and Polypropylene. Issue 1 (February 2021) - Hendrian, Hanoora Sarah Anindita; Saloma,; Hanafiah,; Iqbal, Maulid M.; Juliantina, Ika
Abstract: SCC is a high-performance concrete innovation that does not require vibrating equipment at the time of placement and compaction. The purpose of this study is analysis the ratio effect of fiber gain on physical and mechanical properties of SCC. This research uses fiber with fiber variation and content as additional material. The variation of fiber is pineapple leaf fiber and polypropylene with w/c is 0.3. The variation of fiber has length 12 mm with fiber content 0.2%, 0.3% and 0.4% of cement weight. Testing the physical properties or characteristics of SCC conducted in this study was slump flow, V-funnel and L-box. The testing of mechanical properties performed at the ages of 7 and 28 days for compressive and flexural strength. The addition of fiber showed the effect on physical and mechanical properties of SCC. Increasing the fiber content showed an increase in flexural strength accompanied by a decrease in the value of the diameter and time of fresh concrete. Maximum compressive strength was obtained with the use of 0.3% fiber content of 56.28 and 58.04 MPa for pineapple leaf fiber and polypropylene at the ages of 28 days. The 0.4% fiber content provided a maximum flexural strength of 7.76 and 8.16 MPa for pineapple leaf fiber and polypropylene at the ages of 28 days.